EFEKTIVITAS PENERAPAN SUPERVISI KEPALA RUANG TERHADAP PELAKSANAAN PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RUMAH SAKIT PKU MUHAMMADIYAH BANTUL - Goziyan Goziyan; Elsye Maria Rosa (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2012)
Background: Activity of care documentation is a main element of responsibility for care profession performance. Therefore, treatment supervision is needed in order that effectiveness and efficiency of work are optimum. In approximately recent 4 months, the implementation of treatment supervision in the PKU Muhammadiyah Hospital of Bantul was vacuum, results of interview with the ward heads indicated that there was indication of dissatisfaction of ward head which was also appointed as supervisor in terms of incentive acceptance. Method: This study is quantitative research with quasi experiment pre and post-test design without control group. Respondents of this study were all inpatient ward heads using total sampling. Results and discussion: Results of this study indicated that average percentage of care documentation (standard operational procedure) implementation before treatment supervision training in the inpatient wards of PKU Muhammadiyah Hospital of Bantul was 42.6%, and after training, the percentage was 51.4%. Based on results of statistical test with paired t-test, it was found that p-value of effectiveness of ward head supervision application on implementation of care documentation in the inpatient ward s of PKU Muhammadiyah Hospital of Bantul was 0.002 (p<0.05). There was 8.8% increase in average percentage of care documentation implementation before and after ward head supervision training. Conclusion: The ward head supervision training was found effective on implementation of care documentation in the inpatient wards of PKU Muhammadiyah Hospital of Bantul.